Palmer Amaranth (Amaranthus palmeri) Adaptation to US Midwest Agroecosystems - Oliveira, Maxwel C.; Jhala, Amit J.; Bernards, Mark L.; Proctor, Christopher A.; Stepanovic, Strahinja; Werle, Rodrigo (Frontiers in Agronomy, 2022)
Palmer amaranth (Amaranthus palmeri S. Watson) is one of the most troublesome agronomic weed species in the United States. Palmer amaranth is prevalent in the Southern Great Plains and Southeastern United States, and its range is expanding northward through natural dispersal and human intervention. Palmer amaranth dispersal warrants studies assessing species adaptation into new geographies. A study was conducted to investigate morphology, flowering and gender from cohorts of Palmer amaranth growing under corn, soybean, and bareground across five locations in the US Midwest. Results demonstrated that the first cohort of Palmer amaranth, established in June, produced 42% more biomass than plants from the second cohort (established in July). The first Palmer amaranth cohort produced 75.5 g plant-1 in bareground, 28.3 g plant-1 in soybean and 16.3 g plant-1 in corn, whereas the second Palmer amaranth cohort produced 62.6, 6.3, and 1.4 g plant-1 in bareground, soybean and corn, respectively. Palmer amaranth height was most impacted when growing in corn, and averaged 85.2 cm tall in the first cohort, and 38.2 cm tall in the second cohort in corn. Moreover, Palmer amaranth flowering window shifted according to crop and cohort timings. Palmer amaranth growing in intense competition, such as under low light in corn, resulted in the longest flowering window. Palmer amaranth gender was slightly influenced by day of year, weight and height. We documented a high degree of plasticity in Palmer amaranth, which will presumably favor its adaptation and expansion in cropping systems north of its current range. Therefore, preventing Palmer amaranth dispersal into new habitats is the most effective management strategy.